From History of Development of Some Sacral Concepts with Numerical Component - Abdrazakova А.А.; Akhmetova Б.Б.; Kaskatayeva Ж.А.; Bakenova А.М. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
The history of development of some sacral concepts with components of numerals in Kazakh and English languages is briefly considered in this article. The authors note that the existing semantic field of sacral numerals in stable phrases is associated with the representations of each people in their languages. In Kazakh and English languages numerals are more useful in the formation of phraseological units and are very often found in stable phrases of a national character (namely religious beliefs, customs, rituals, traditions). In the article, on examples of discussion of the frequency use of certain indicators in stable word combinations in legends, epos poems, traditions; determination of the significance of certain numbers depending on a person’s age. When comparing the semantic field of the sacral numerals of Kazakh and English, the authors state more differences than similarities. Such conclusions are made by the authors on the basis of the analysis of phraseological units and proverbs of the both languages